(3GdeSFhdjI GdbGfhfjI ddSeSGQ Yf YedjGJ GdHhQUI (B: s (3OQGSI ebGQfI (B/ s - (3CSGeI YOfGf GdMdjHjs; (3SejMI eUWai GdbdjhHj s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2013)
(3JfGhdJ GdOQGSI ehVhY GdeSDhdjI GdbGfhfjI ddSeSGQ Yf YedjGJ GdHhQUI h JfGhd GdHGMK ehVhY eGgjI SeSGQ GdChQGb GdeGdjI h WHjYJg GdbGfhfjI h Mbhb hhGLHGJ GdSeSGQ Yf Jdc GdYedjGJ Ke JYQV GdHGMK ai TiA ef GdJaUjd ai GdaUd GdChd dehVhY GdeSDhdjI GdeOfjI dSeSGQ GdChQGb GdeGdjI h gfG JfGhd GdeSDhdjI GdYbOjI h cPdc GdeSDhdjI GdJbUjQjI h cPdc Ydi hLg GdNUhU MGdGJ bjGe GdeSDhdjI GdJbUjQjI h cPdc GdJYhjV h HYOgG JfGhd GdeSDhdjI GdJCOjHjI dSeSGQ GdChQGb GdeGdjI h Hjf GdQbGHI Ydi TQcGJ GdSeSQI ai eUQ cCSGS dgPg GdeSDhdjI hcPdc GdQbGHI Ydi TQcGJ GdSeSQI ai aQfSG h ajeG jNU GdLRGAGJ GdJCOjHjI JfGhd CfhGY GdLRGAGJ GdJCOjHjI ai eLGd Shb QCS GdeGd h cPdc WQb GdWYf Ydi GdLRGAGJ GdJCOjHjIs
(3CWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdJLGQj (B2013.s
(3HHdjhLQGajG(B: (3UaMGJ (B174-182.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdQbGHI s; (3SeSGQ GdChQGb GdeGdjIs; (3GdeSFhdjI GdeOfjI dSeSGQ GdChQGb GdeGdjIs; (3GdeSFhdjI GdJCOjHjI dSeSGQ GdChQGb GdeGdjIs; (3GdWYf Ydj GdLRGAGJ GdJCOjHjI aj eLGd GdChQGb GdeGdjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs